Incidence of cutaneous manifestation in patients with end stage renal disease - Singh, Khileshwar; Thakur, Amit; Dhruv, Kamlesh (International Journal of Advances in Medicine, 2017)
Background: Kidney failure as well as renal diseases is the most important health problems affecting the middle and old age population all over the world. They were supposed to be fatal till recently. The objective of this study was to study incidence of cutaneous manifestation in patients with end stage renal disease. Methods: A hospital based cross sectional study was carried out from July 2012 to June 2013 in the Department of General Medicine, Late Baliram Kashyap Memorial Government Medical College, Jagdalpur, Chhattisgarh, India. It was possible to study a total of 50 cases of cutaneous manifestations that are already known cases of end stage renal disease. All patients with skin lesion were evaluated by history, clinical examination (systemic and dermatological), biopsy and other relevant investigations procedure for skin disease during the course of current renal disease and their stay in the hospital. Results: The incidence of cutaneous manifestations among patients with acute renal failure was zero. It was 86% among patients with chronic renal failure. The most common manifestation was pruritus in 14% of cases followed by oral candidiasis in 4% of cases. Next common was scabies in 6% of cases and this was followed by herpes zoster and Tinea cruris in 4% of cases each. Folliculitis was seen in only one case. It was seen that all types of cutaneous manifestations were present only in patients with chronic renal failure, whereas patients of acute renal failure did not show any sort of cutaneous manifestations. Conclusions: Chronic renal failure was observed as the important cause of cutaneous manifestations seen in patients with end stage renal disease. No cases were seen in patients with acute renal failure. Thus, it is important that patients with acute renal failure take proper precautions to avoid cutaneous manifestations up to the extent possible.